Processing Rice Land to Increase Rice Food Security in Semarang City: (Location study Purwosari Village) - Hendri Wibowo,; Dewi Hastuti,; Ahmad Abdul,; Istanto,; Rossi Prabowo,; Endah Sukbekti,; Shofia Nur Awami, (Journal Galung Tropika, 2024)
This research aims to understand the influence of five production factors, namely land area, urea fertilizer, NPK fertilizer, labor, and pesticides, on the amount of rice production in Purwosari Village, Semarang. The method used is a case study involving 61 rice farmers in the village. Data analysis was carried out using the Cobb-Douglas production function, production scale, and economic efficiency. The research results show that all production factors together have a very significant influence on the amount of rice production. However, when analyzed individually, only land area, urea fertilizer, and NPK fertilizer had a significant effect. Labor and pesticides did not show a significant effect on rice production. The scale of rice production in Purwosari shows an increasing trend. The economic efficiency of using production factors shows that the use of land, urea fertilizer, and NPK fertilizer has not reached optimal levels (NPM/BKM >1). On the other hand, the use of labor and pesticides is classified as inefficient (NPM/BKM <1). In conclusion, this research recommends increasing land use, urea fertilizer, and NPK fertilizer to increase rice production in Purwosari. On the other hand, the use of labor and pesticides needs to be optimized to achieve better efficiency.